A retrospective, single-center 4-year review of synthetic polyurethane matrix use in burns and other complex wounds - Muntazim Mukit; Payton Grande; David Hill; Kalyan Dadireddy; Sai Velamuri; Mahmoud Hassouba; Xiangxia Liu (Elsevier, 2024)
Here we describe the use of a synthetic polyurethane matrix in the setting of burns and other complex wounds in the largest United States case series to date. A retrospective review was conducted at a verified, regional burn center. All patients greater than 18 years of age who received this matrix between January 2019 and July 2023 were included. A total of 182 patients with 250 wounds were included in this study. Thirty-seven percent were smokers, 23.6 % had diabetes and 5.5 % had peripheral vascular disease. The majority were acute burn wounds (60 %), followed by trauma (24.4 %), chronic wounds (5.6 %), infection (4 %) and donor sites (2 %). Exposed structures included fat (54 %), muscle (30 %), bone (16 %) and tendon (14.4 %). Microbial colonization was present in 143 (57.2 %) of cases: 98 (39.2 %) pre-application and 89 (35.6 %) post application. The incidence of new microbial colonisation post-application was 25.6 %. Infection was present in 117 (46.8 %) cases, 49 (19.6 %) pre-matrix application, 44 (17.6 %) post-matrix application and 24 (9.6 %) pre and post application. Eighteen patients (10 %) died. Median length of stay was 27 days. Median time to matrix implantation was 10 days. Median time from matrix placement to skin grafting was 35 days. Where documented, there were 162 wounds (83.5 %) with > 95 % matrix survival and 136 wounds (82.4 %) with > 95 % skin graft survival even in the setting of adverse factors such as infection, diabetes, or nicotine use. This study demonstrates the robustness of this skin substitute to achieve successful reconstruction even in the setting of adverse patient or wound characteristics.